(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
Objective: To assess the socio-demographic profile of Ashmari vis-Ã -vis Urolithiasis patients in a tertiary care hospital. Methods: This was a cross-sectional study. Patients suffering from silent features of Mutrashmari described in Ayurvedic and Modern texts attending the O.P.D. and I.P.D. of a tertiary care hospital were selected (age 21-60 years) for the study. The diagnosis was made by radiological (plain X-ray, intravenous urography) and sonological (ultrasonography). Results: More than one third of Ashmari patients were between 31-40 years (40%). More than half of Ashmari patients were males (53.3%). Desk work occupation was most common (36.7%). More than half of Ashmari patients were educated high school & above (63.3%). Majority of Ashmari patients were married (83.3%) and belonged to above poverty line (96.7%). Majority of Ashmari patients took routine food (80%) and were mixed type of diet (70%). Fluid intake was <3 liters per day among majority of Ashmari patients (73.3%). Conclusion: Males formed the majority of patient with Ashmari/urolithiasis with commonest age group of 31-40 years. Larger studies are however recommended to confirm this observation.